Knowledge Management in Practice A Critique on the Book Knowledge Strategy and Knowledge Management - Mohammad Hassanzadeh; Behrouz Rasouli; Somayeh Jafari (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Many researchers, professionals, and managers believe that knowledge is one of the key assets of organizations and businesses in the current era. In this regard, the term knowledge strategy has been considered in order to clarify the knowledge assets for the organization, which ultimately improves the efficiency and effectiveness of the organization by implementing knowledge management and formulating a knowledge management strategy. The book Knowledge Strategy and Knowledge Management seeks to explain two main concepts, namely “Knowledge Strategy” and “Knowledge Management Strategy” in four chapters. This book is one of the first works in the Persian language to focus on the concept of knowledge strategy. Although the book addresses an important issue that is one of the key needs business managers, the distinction between strategic management, knowledge strategy, strategic knowledge management, etc. is not clearly stated. The purpose of this article is to review the book Knowledge Strategy and Knowledge Management from different aspects.